The Basic Directions of Economic Decisions of Social Problems in the East African Countries (Burundi, Uganda, Rwanda) - F Mutemberezi (RUDN Journal of Economics, 2009)
Now Rwanda, Burundi and Uganda as a whole, form the considerable potential consumer market. Its activization depends on the desire from outside political leaders to integrate the general consumer market (through economic integration) and to realize the adequate economic policy in each country by promoting to raise real incomes of peasants. It is possible to assert unequivocally that a prime problem of these countries at the present stage is social, which means fight against poverty of mass ordinary people.